Characterization of reduced graphene oxide obtained from vacuum-assisted low-temperature exfoliated graphite - Gopinath, S.C.B. (Springer Verlag, 2018)
Graphene consists of sheets of two-dimensional allotrope carbons and is a basic element of graphite. Herein, reduced graphene oxide (rGO) were exfoliated from graphite material under vacuum and low temperature and characterized by scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction and Fourier transform infrared spectroscopy (FTIR). The results revealed that the obtained rGO is morphologically well structured in the size ranges of 1â3 Âµm and smooth. An apparent reduction of O1s with XPS analysis was noticed. The crystalline nature of rGO was evidenced by (0 0 2) and (0 0 4) orientations. FTIR has generated clear peak stretches at 1018, 1092 and 1628 cmâ1. Further, UVâvisible and Raman spectroscopic optical analyses displayed the apparent peak profiles at appropriate positions. The appearance of G and D bands with the respective G/D ratio of peak intensity in Raman analysis aids to estimate D/G to be ~ 0.8. The calculated ratio with 2D/G is to be 1.7 with a single layer of graphene. Overall, the results of this study demonstrated that rGO can be obtained simply by vacuum assisted a low thermal exfoliation. Â© 2018 Springer-Verlag GmbH Germany, part of Springer Nature